Implementation of Policy of Fulfilling of People’s Rights with Mental Disorder in the West Java Province, Indonesia - Anggara, Sahya (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study was to analyze the implementation of policies on fulfilling the rights of people with mental disorders in West Java Province and the factors that influence them. The research method used in this study is a qualitative method. This research data collection using in-depth interview techniques, observation and study documentation. Data analysis was performed using the Milles & Huberman triangulation technique. Based on the results of the study note that the implementation of the policy fulfillment of the rights of people with mental disorders in West Java Province is still not optimal, this is due to the factor of minimal resources to run mental health services. In addition, there are still problems relating to the economic, social and political environment in fulfilling the rights of people with mental disorders.